Kajian Aplikasi Kompos Sampah Organik Perkotaan untuk Tanaman Bawang Merah pada Sistem Urban Farming: Study of The Application of Urban Organic Waste Compost for Shallot Cultivation in an Urban Farming System - Haryanta, Dwi; Suryaningsih, Dwie Retna; Fauzi, Muhammad Iqbal (Agrocentrum, 2025)
The problem of accumulating organic waste can be solved by converting it into compost and can be used to strengthen food security in urban areas. The purpose of this research is to find a solution to the problem of urban organic waste burden into an economically valuable resource by processing it into compost, studying the effect of urban organic waste compost on the growth and yield of vegetable plants (shallots), and providing a fertile and affordable planting medium, reducing dependence on conventional fertilizers that must be imported from outside the city. Research on the application of compost produced from a compost house for shallot plants with 4 treatments: pure soil planting medium, soil planting medium plus leaf compost, soil planting medium plus young coconut fiber compost, and soil planting medium plus rain tree leaves. The study used a randomized block design with seven replications. The results of the study were that the best growth and yield of shallot plants were obtained from plants planted in soil media without being mixed with compost, while the worst were from plants planted in soil media with fresh rain tree leaf compost. The conclusion of the study was that the compost used was not yet mature because the composting process was only 28-35 days, or with rain tree leaves without a composting process. The use of immature compost or organic material that has not fully decomposed will actually have a negative impact on plants. Plants and microbes compete for nutrients or plants can be poisoned by compounds produced by the composting process (such as ammonium compounds). The implication of this research is that compost utilization will have a positive impact when the compost is fully mature. Compost producers, such as compost houses or recycling centers (PDU) in Surabaya, should release mature compost or socialize to the public that compost produced from compost houses needs to be incubated for at least 30 days before it can be used for urban farming activities.